A square VO2 nanosheet and its preparation method and application
The preparation of square VO2 nanosheets with monoclinic metastable phases by hydrothermal method solves the poor controllability and environmental protection problems of VO2 preparation process in the prior art, and realizes the efficient performance of VO2 in photocatalytic degradation of antibiotics.
Patent Information
- Application Number
- CN202210563697.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-05-23
AI Technical Summary
In the existing VO2 preparation methods, the reaction process is poorly controlled, the use of strong reducing agents leads to harsh preparation conditions, and environmental protection problems. At the same time, the morphology of VO2 limits its catalytic activity against antibiotic degradation.
The hydrothermal method was used to dissolve vanadyl acetylacetonate in a mixed solution of isopropanol and water, and hydrothermal reactions were carried out at 180-190°C to prepare a square VO2 nanosheet with a monoclinic metastable phase. This method avoids the use of highly toxic organic solvents and strong oxidative co-solvents, simplifies process operations and reduces risk.
The prepared VO2 nanosheets have excellent photocatalytic properties, have a high degradation rate for organic pollutants such as antibiotics under visible and near-infrared light, and the process is more environmentally friendly and safe.
Smart Images

Figure HDA0003657447280000011 
Figure HDA0003657447280000012 
Figure HDA0003657447280000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials and relates to a square VO2 nanosheet and a preparation method and application thereof. Background Art
[0002] VO2 is a dark blue crystalline powder that is insoluble in water but soluble in acid and alkali. It has multiple crystal phases, the most common of which are tetragonal rutile VO2(R)(P42 / mnm), monoclinic VO2(M)(P21 / c) and at least three metastable phases, namely VO2(B)(C2 / M), VO2(A)(P42 / nmc) and VO2(C). These crystal forms are based on VO6 octahedron as the basic unit, among which V 4+ Occupies the center of the octahedron, each V 4+ By six O 2- Surrounded. The octahedra are arranged by sharing edges or vertices, and rely on a certain symmetry form to form a long-range ordered structure in three-dimensional space. Due to the different shapes of the internal VO6 octahedrons and the different ways of linking the octahedra, VO2 crystals of different crystal forms have different atomic coordinates and spatial symmetry groups.
[0003] Monoclinic metastable VO2(B) has attracted great attention due to its layered structure and unique optical properties. It has the advantages of low cost, relatively low toxicity, excellent carrier transport channel, high energy capacity and medium work potential, and has broad application prospects in the field of energy technology. VO2(B) is both energy-saving and environmentally friendly. Its photocatalytic behavior combined with other nanomaterials will cause the energy band alignment between VO2(B) and pollutant molecules, thereby promoting the separation of photogenerated electron-hole pairs, the generation of photogenerated charges, and reducing the recombination rate of photogenerated electron-hole pairs.
[0004] At present, VO2 is mainly prepared by chemical synthesis, using pentavalent vanadium compounds as precursors and adding suitable reducing agents. However, due to the multiple valence states of vanadium, it is difficult to control the synthesis and microstructure of VO2. The existing chemical synthesis method often requires the addition of strong reducing agents, resulting in poor controllability of the reaction process and harsh reaction conditions for the production of VO2.
[0005] Patent CN112174206A discloses a method for directly preparing vanadium dioxide using acetylacetonato vanadyl as a vanadium source, wherein VO2 is prepared using highly toxic organic matter as a solvent. Patent CN104724757B discloses a method for directly synthesizing rutile phase vanadium dioxide nanopowders at low temperature based on solvothermal method, wherein a co-solvent with strong oxidizing properties is added while using a solvent. Since the solvent used has a low flash point, the presence of a co-solvent with strong oxidizing properties increases the danger in the preparation process. In addition, both of the above two published patents use solvothermal method, which involves the use of organic solvents, which is not conducive to environmental protection.
[0006] In addition, there are few reports on the catalytic activity of VO2 in the degradation of antibiotics, mainly because the common morphology of VO2 is rod-shaped and snowflake-shaped, and it has problems such as small specific surface area, few active sites, and low photon utilization rate, which makes its degradation effect on antibiotics not ideal. Summary of the invention
[0007] The purpose of the present invention is to provide a square VO2 nanosheet and its preparation method and application. The monoclinic metastable VO2 nanosheet is prepared by a hydrothermal method with a simpler preparation process and less risk. The obtained monoclinic metastable phase VO2 nanosheet has excellent photocatalytic performance under visible light and near-infrared light, and is more environmentally friendly.
[0008] The present invention is achieved through the following technical solutions:
[0009] A method for preparing a square VO2 nanosheet comprises the following steps:
[0010] Step 1, dissolving vanadyl acetylacetonate in a mixed solution of isopropanol and water, and stirring to form a precursor solution A;
[0011] Step 2, transferring the precursor solution A into a polytetrafluoroethylene-lined autoclave for hydrothermal reaction at 180-190° C., and centrifuging to obtain a precipitate;
[0012] Step 3, washing the precipitate after centrifugation with deionized water and anhydrous ethanol, and drying to obtain pure phase VO2 nanosheets.
[0013] Preferably, in step 1, the ratio of vanadyl acetylacetonate to the mixed solution is (0.275-0.277) mmoL: (30-35) mL.
[0014] Preferably, in step 1, the volume ratio of isopropanol to water is (2-5):1.
[0015] Preferably, in step 1, the stirring time is 30 to 60 minutes.
[0016] Preferably, in step 2, the filling amount of the precursor solution A in the polytetrafluoroethylene liner is 70%;
[0017] Preferably, in step 2, the hydrothermal time is 3 to 4 hours.
[0018] Preferably, in step 3, the drying is performed under vacuum at 50-60° C. for 10-12 hours.
[0019] The square VO2 nanosheets are used as photocatalysts in the photocatalytic degradation of organic pollutants.
[0020] The square VO2 nanosheets are used as photocatalysts in the photocatalytic degradation of antibiotics.
[0021] Compared with the prior art, the present invention has the following beneficial technical effects:
[0022] The present invention provides a method for preparing VO2 nanosheets, which uses a certain proportion of water added to isopropanol to form a hydrothermal system, and prepares monoclinic metastable tetragonal VO2 nanosheets through a hydrothermal method. The preparation method used in the present invention has the advantages that: on the one hand, the solvent in the reaction system is formed by adding water to isopropanol, instead of using highly toxic organic solvents such as toluene, tetrahydrofuran, dioxane, N,N-dimethylformamide or dimethyl sulfoxide, which is more green and environmentally friendly; on the other hand, there is no need to add strong oxidizing co-solvents such as hydrogen peroxide, dilute hydrochloric acid and sodium hydroxide during the preparation process, the process operation is simple, and the danger of the experimental process is reduced. In addition, compared with other preparation methods, the monoclinic metastable VO2 nanomaterial synthesized by the one-step hydrothermal method has good crystal development, high purity, and controllable size, avoiding impurities and structural defects caused by post-treatments such as high-temperature calcination or ball milling. Since the precursor solution contains a large amount of ·OH, ·OH will preferentially adsorb on some crystal faces of the VO2 crystal nucleus and reduce the surface energy. The growth rate of these crystal faces will decrease accordingly. As the hydrothermal growth time increases, the VO2 particles will consume small particles and further grow into VO2 nanosheets.
[0023] The monoclinic metastable VO2 nanosheets prepared by the present invention have a large specific surface area and many active sites, which can increase the adsorption amount of pollutants, and are beneficial to further degradation of pollutants, thereby improving the photocatalytic activity of VO2.
[0024] The VO2 nanosheets prepared by the present invention have a high degradation rate for organic pollutants such as antibiotics under visible light-near infrared light. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the XRD pattern of the monoclinic metastable tetragonal VO2 nanosheet prepared by the present invention;
[0026] Figure 2 is a SEM image of the monoclinic metastable tetragonal VO2 nanosheet prepared by the present invention;
[0027] Figure 3 This is the degradation curve of TC degradation under visible light by the monoclinic metastable tetragonal VO2 nanosheet prepared by the present invention;
[0028] Figure 4 This is the degradation curve of TC degradation under near-infrared light by the monoclinic metastable tetragonal VO2 nanosheet prepared by the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0030] Example 1
[0031] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0032] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0033] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0034] Example 2
[0035] Step 1, dissolving 0.275 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0036] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0037] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0038] Example 3
[0039] Step 1, dissolving 0.277 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0040] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0041] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0042] Example 4
[0043] Step 1, dissolving 0.276 mmol of vanadium acetylacetonate in a mixed solution of 24 mL of isopropanol and 8 mL of water, and stirring for 40 min to form a precursor solution A;
[0044] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0045] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0046] Example 5
[0047] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 26.25 mL of isopropanol and 8.75 mL of water, and stirring for 40 min to form a precursor solution A;
[0048] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0049] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0050] Example 6
[0051] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 30 min to form a precursor solution A;
[0052] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0053] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0054] Example 7
[0055] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 50 min to form a precursor solution A;
[0056] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0057] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0058] Example 8
[0059] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 60 min to form a precursor solution A;
[0060] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0061] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0062] Example 9
[0063] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0064] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 180° C. for 3 h, and centrifuging to obtain a precipitate;
[0065] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0066] Example 10
[0067] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0068] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 185° C. for 3 h, and centrifuging to obtain a precipitate;
[0069] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0070] Embodiment 11
[0071] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0072] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3.5 hours, and centrifuging to obtain a precipitate;
[0073] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0074] Example 12
[0075] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0076] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 4 hours, and centrifuging to obtain a precipitate;
[0077] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 12 h to obtain square VO2 nanosheets.
[0078] Example 13
[0079] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0080] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0081] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 50° C. for 12 h to obtain square VO2 nanosheets.
[0082] Embodiment 14
[0083] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0084] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0085] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 55° C. for 12 h to obtain square VO2 nanosheets.
[0086] Embodiment 15
[0087] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0088] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0089] Step 3, the precipitate after centrifugation is washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 10 h to obtain square VO2 nanosheets.
[0090] Example 16
[0091] Step 1, dissolving 0.276 mmol of vanadyl acetylacetonate in a mixed solution of 22.5 mL of isopropanol and 7.5 mL of water, and stirring for 40 min to form a precursor solution A;
[0092] Step 2, placing the precursor solution A in a hydrothermal reactor, with the filling amount of the precursor solution A in the polytetrafluoroethylene liner being 70%, hydrothermally reacting at 190° C. for 3 h, and centrifuging to obtain a precipitate;
[0093] Step 3, the precipitate after centrifugation was washed three times with deionized water and anhydrous ethanol respectively, and then vacuum dried at 60° C. for 11 h to obtain square VO2 nanosheets.
[0094] Figure 1is the XRD pattern of the monoclinic metastable tetragonal VO2 nanosheets prepared in Example 1. It can be seen from the figure that the diffraction peaks at 14.38°, 15.31°, 25.24°, 29.00°, 30.29°, 33.75°, 44.12°, 44.95° and 49.18° correspond to VO2 (JCPDS No.81-2392) has diffraction peaks on the (001), (200), (110), (002), (111), (-311), (003), (-601), and (020) planes, and no other diffraction peaks were observed, indicating that the prepared VO2 is a monoclinic metastable phase, which belongs to the C2 / m type space group, and its specific unit cell parameters are: a=12.093, b=3.7021, c=6.433, α=90.0°, β=106.97°, γ=90.0°.
[0095] Figure 2 This is a SEM image of the monoclinic metastable tetragonal VO2 nanosheets prepared in Example 1. The VO2 is in the shape of a tetragonal sheet with a size of 500×600nm to 900×800nm.
[0096] Figure 3 This is the degradation spectrum of tetracycline (TC) degradation under visible light by the monoclinic metastable tetragonal VO2 nanosheets prepared in Example 1. A 20 mg / L TC aqueous solution was prepared, and the reaction was first carried out in the dark for 30 minutes. After reaching the adsorption-desorption equilibrium, the light reaction was carried out. It can be seen from the figure that in the absence of any photocatalyst, the self-degradation efficiency of TC is extremely low and can be ignored. Therefore, the removal of TC comes from the photodegradation effect of the photocatalyst. The degradation curve of the sample under visible light shows that TC is degraded to a certain extent after visible light irradiation. The degradation rate of TC by the VO2 nanosheet photocatalyst after 120 minutes of visible light irradiation reaches a maximum of 75.69%, indicating that the degradation rate of the VO2 nanosheet is high and has good photocatalytic performance.
[0097] Figure 4 This is the degradation spectrum of TC degradation under near-infrared light by the monoclinic metastable tetragonal VO2 nanosheets prepared in Example 1. A 20 mg / L TC aqueous solution was prepared and reacted in the dark for 30 minutes. After reaching the adsorption-desorption equilibrium, the light reaction was carried out. It can be seen from the figure that in the absence of any photocatalyst, the self-degradation efficiency of TC is extremely low and can be ignored. Therefore, the removal of TC comes from the photodegradation effect of the photocatalyst. After the sample was irradiated with near-infrared light for 120 minutes, the degradation rate of TC by the VO2 nanosheet photocatalyst reached a maximum of 60.37%, indicating that the VO2 nanosheet has good photocatalytic activity under near-infrared light.
[0098] The above contents are further detailed descriptions of the present invention in combination with specific preferred implementation modes, and are not all or the only implementation modes. Any equivalent changes made to the technical solutions of the present invention by ordinary technicians in this field after reading the specification of the present invention are covered by the claims of the present invention.
Claims
1. A method for preparing square VO2 nanosheets, characterized in that: The following steps are involved: Step 1, dissolving vanadyl acetylacetonate in a mixed solution of isopropanol and water, and stirring for 30 to 60 minutes to form a precursor solution A; Step 2, hydrothermally reacting the precursor solution A at 180-190° C. for 3-4 hours, and separating to obtain a precipitate; Step 3, washing the obtained precipitate and drying it to obtain square VO2 nanosheets; In the step 1, the ratio of vanadyl acetylacetonate to the mixed solution is (0.275-0.277) mmoL: (30-35) mL, and the volume ratio of isopropanol to water is (2-5):
1.
2. The method for preparing the square VO2 nanosheets according to claim 1, characterized in that: In step 3, washing is performed with deionized water and anhydrous ethanol in sequence.
3. The method for preparing the square VO2 nanosheets according to claim 1, characterized in that: In step 3, the drying is performed under vacuum at 50-60° C. for 10-12 hours.
4. The square VO2 nanosheet obtained by the preparation method according to any one of claims 1 to 3, characterized in that: The VO2 structure is a monoclinic metastable phase and its morphology is a square nanosheet.
5. Use of the square VO2 nanosheets described in claim 4 as a photocatalyst in photocatalytic degradation of organic pollutants.
6. The use according to claim 5, characterized in that: The organic pollutant is an antibiotic.
Citation Information
Patent Citations
Method for directly synthesizing rutile-phase vanadium dioxide nano powder by low-temperature solvothermal method
CN104724757B
Method for directly preparing vanadium dioxide by taking vanadiumoxy acetylacetonate as vanadium source
CN112174206A
Synthetic method for dimension-controllable vanadium dioxide nano material, and lithium ion battery
CN105836800A
Hydrothermal synthesis method of monoclinic phase vanadium dioxide nano-powder
CN110759382A